Wool studio : the knit-wear capsule collection - Babin, Meghan (Interweave, an imprint of F + W Media, 2018)
A collection of patterns for sophisticated, simple knitwear designed for the modern woman. Each design element has been selected to showcase the yarns, creating contemporary yet minimalist fashions that will outlast the trends of the day. -- adapted from introduction.